2018
DOI: 10.2217/nnm-2018-0297
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Biodegradable Nanoparticles-in-Nanofibers Single-Dose Ocular Insert: In Vitro , Ex Vivo and In Vivo Evaluation

Abstract: Aim: This study involves, for the first time, the development of mucoadhesive biodegradable polymeric-multilayered nanoparticles-in-nanofibers (NPs-in-NFs) matrix as an innovative single-dose noninvasive ocular-insert that could substitute conventional ocular dosage-forms. Materials & methods: Azithromycin-loaded poly(lactic-co-glycolic acid) copolymer/pluronic NPs were developed then incorporated into electrospun polyvinylpyrrolidone NFs, and tested for their efficient treatment of ocular bacterial infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 48 publications
4
18
0
Order By: Relevance
“…Tensile strength was tested at 5 kN with 10 mm/min rate using universal testing machine (AGX-PLUS, Shimadzu, Japan). Each sample was cut into a rectangle with thickness × width × length (0.5 × 5 × 20 mm) . Porosity of the fabricated NFs (1 cm × 1 cm of known weight) was investigated using a pycnometer (Ultrapyc 1200e, Quantachrome Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…Tensile strength was tested at 5 kN with 10 mm/min rate using universal testing machine (AGX-PLUS, Shimadzu, Japan). Each sample was cut into a rectangle with thickness × width × length (0.5 × 5 × 20 mm) . Porosity of the fabricated NFs (1 cm × 1 cm of known weight) was investigated using a pycnometer (Ultrapyc 1200e, Quantachrome Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…The formulations were characterized in vitro, ex vivo, and in vivo. The results showed improved bioavailability, low risk of toxicity, and prolonged drug release over 10 days [ 56 ]. Two polymer series, polycaprolactone (PCL) and polyvinyl alcohol (PVA), were used to formulate biodegradable polymeric patches containing timolol maleate and dorzolamide hydrochloride for cul-de-sac insertion.…”
Section: Resultsmentioning
confidence: 99%
“…The drug release and permeation profile established that ocular insert could render controlled drug release upto 10 days. The authors concluded that the incorporation of NPs into NFs could achieve many advantages such as increased ocular residence due to better contact with conjunctiva, accurate dosage, prolonged drug release, reduced dosing frequency, reduced systemic side effects, and improved bioavailability [ 64 ].…”
Section: Recent Advancements In Ocular Deliverymentioning
confidence: 99%